A new species of parrot snake, Leptophis (Serpentes: Colubridae) from the Brazilian Cerrado - Nelson R. Albuquerque; Roullien H. Martins; Priscila S. Carvalho; Donald B. Shepard; Diego J. Santana (PeerJ)
We describe a new species of Leptophis (parrot snake) from the Cerrado ecoregion of Brazil. The new species, L. mystacinus sp. nov., differs from all other congeners in the following unique character combination: two Spectrum Green (129) to Light Parrot Green (133) dorsolateral stripes separated by a Buff (5) vertebral stripe, usually continuous onto the tail; loreal scale absent; postocular stripe Jet Black (300), wide and long (up 11 scales long onto nuchal region); maxillary teeth 21–25; ventrals 158–173; subcaudals 141–164; black spots on head absent; supracephalic plates of head not edged with black pigment; adult color pattern lacking dark oblique bands; keels absent on first dorsal scale rows; hemipenis unilobed, noncapitate, with undivided sulcus spermaticus, and first row of hemipenial body with four spines. Phylogenetic analysis of 16S mtDNA sequences indicate the new species is the sister taxon of L. dibernardoi, a species occurring in the neighboring Caatinga ecoregion.